Implikasi TRA (Theory Of Reasoned Action) dan TAM (Technology Acceptance Model) pada Pengguna Layanan Perbankan Online - Defa Septia (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2023)
In this modern era, the use of online banking has widely used by some people. Almost all banks have facilitated their customers with this online banking service. The use of online banking can be influenced by factors that are supportive or unsupportive. The objective of this study is to assess the consequences of the theory of reasoned action (TRA) and the theory acceptance model (TAM) on the adoption and usage of online banking services in the city of Bandar Lampung. The variables under investigation in this study encompass attitude, subjective norms, convenience of use, and perceived utility. The participants in this study consist of individuals who utilise autonomous online banking services in the region of Bandar Lampung. The present study employed an incidental sampling technique, wherein a total of 100 respondents were included in the sample. Prior to doing hypothesis testing, it is customary to perform reliability and validity tests on the data. The data was thereafter subjected to analysis through the utilisation of multiple linear regression techniques employing the Statistical Package for the Social Sciences (SPSS). The findings of this study indicate that of the four variables examined, only one element, namely simplicity of use, demonstrates a statistically significant impact on the adoption of online banking. The variables of attitude, subjective norms, and perceived utility do not exhibit a statistically significant impact on the adoption of independent internet banking in the context of Bandar Lampung.